Culturally Based Practice in Neonatal Procedural Pain Management: A Mini Review - Fitri, Siti Yuyun Rahayu; Wardhani, Viera; Rakhmawati, Windy; Pahria, Tuti; Hendrawati, Sri (Frontiers in Pediatrics, 2020)
Cultural factors have gradually become important considerations in health services, including in pain management for adult and pediatric patients. However, research on culturally based pain management in neonates remains limited. This mini review aims to provide an overview of procedural pain management in neonates based on cultural approaches from various countries. The review found that there are several analyses of pain management procedures for neonates developed from cultural practices, namely, acupuncture, foot massage and reflexology, Yakson touch therapy, and aromatherapy. The acupuncture method (invasive and noninvasive) is more widely studied using randomized controlled trials (RCTs) than the other methods because the techniques applied can be standardized and measured. There are indications of the positive impact of all the methods examined in this review, but the results of studies have not been consistent because of the diversity of outcome measurement methods used and because of the difficulty of creating standardized procedures to measure pain management methods that are based on cultural practices